Pre-clinical studies comparing the anti-inflammatory potential of artemisinic compounds by targeting NFκB/TNF-α/NLRP3 and Nrf2/TRX pathways in Balb/C mice - Kazmi, Syeda Tayyaba Batool; Fatima, Humaira; Naz, Iffat; Kanwal, Nosheen; Haq, Ihsan-ul (Frontiers in Pharmacology, 2024)
Artemisinin, artemether, artesunate, and dihydroartemisinin are renowned for their antimalarial potential. The current study aims to repurpose the above-mentioned artemisinic compounds (ACs) by conducting an intercomparison to evaluate their antiinflammatory potential (AIP). In order to develop potential candidates for the evaluation of AIP of ACs (50 and 100 mg/kg BW), carbon tetrachloride (1ml/kg body weight (BW)) was administered intraperitoneally to BALB/c mice. Alterations in animal behavior were assessed weekly through tail suspension test, force swim test, open field test, Y-maze test, inverted screen analysis, and weight lifting test. Aberrations in hematological, serological, endogenous antioxidants, and oxidative stress marker profiles were assessed in all twelve groups. Histological alterations were read using hematoxylin and eosin staining. Levels of inflammatory markers including nuclear factor kappa B (NF-κB), tumor necrosis factor alpha (TNF-α), and nucleotide-binding oligomerization domain-like receptor protein 3 (NLRP3), were determined using immunohistochemical analysis (IHCA). Antioxidant markers i.e., nuclear factor erythroid-2-related factor (Nrf-2) and thioredoxin (TRX) were also quantified through IHCA. Comet assay was performed to quantify DNA damage. Oral administration of ACs to mice significantly alleviated the carbon tetrachloride induced inflammation in comparison with silymarin. Reduced levels of several inflammatory markers including nitric oxide, thiobarbituric acid reactive substances, interleukin-1 beta, NF-κB, TNF-α, and NLRP3, underscore the substantial AIP of ACs. IHCA depicted the revitalized percent relative expression of Nrf-2 and TRX in groups treated with ACs. Behavioral analysis revealed that ACs-treated groups significantly (p<0.05) attenuated the memory deficit, anxiety, and depressive-like behavior. Moreover, histopathological, hematological, serological, and endogenous antioxidant profiles indicated substantial AIP of ACs. Findings of comet assay further bolstered the compelling evidence as DNA damage was significantly (p<0.05) curbed down after ACs (100 mg/kg) treatment. All these outcomes implied that ACs exhibited AIP in a dose-dependent manner with maximal AIP imparted by artemisinin (100 mg/kg). This pre-clinical investigation avers the tremendous AIP of ACs targeting key molecular pathways. The current study divulges artemisinin as the most potent antiinflammatory agent among the tested compounds.